Silver Nanoparticles 2010
DOI: 10.5772/8509
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Silver Nanoparticles as an Additive in Animal Feeding

Abstract: Among other uses, metallic silver and silver salts have currently been applied as antimicrobial agents in many aspects of medical industries, such as coating of catheters, dental resin composites and burn wounds, as well as in homeopathic medicine, with a minimal risk of toxicity in humans. However, their use in animal feeding as prebiotics have remain minimised, mostly because of the low cost antibiotics used as growth promoters in the second half of the XX Century. However, after the ban of this practice in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 50 publications
1
33
0
1
Order By: Relevance
“…Analysis of various species including various strains of rats, mice, piglets etc., showed variable results [61,146]. Ag NPs were found to be accumulated in various organs of mammals, such as lung, kidney, liver, spleen, brain, and heart [147].…”
Section: Toxic Response Of Ag Nps Against Mammalian Modelsmentioning
confidence: 98%
“…Analysis of various species including various strains of rats, mice, piglets etc., showed variable results [61,146]. Ag NPs were found to be accumulated in various organs of mammals, such as lung, kidney, liver, spleen, brain, and heart [147].…”
Section: Toxic Response Of Ag Nps Against Mammalian Modelsmentioning
confidence: 98%
“…The results of a study of the effect of silver nanoparticles used as an additive in diets for weanling pigs on the digestive microbiota and gut morphology, and in productive performances and silver retention in tissues, suggested that silver effect may be mediated through its antimicrobial properties, either by acting against certain bacterial groups or just reducing the microbial load of the small intestine 231. Silver nanoparticles could be applied to animal feeding232 and are also a potent antimicrobial agent for use in broiler chickens 233. Magnetic nanoparticles were found successful for the recovery of aflatoxin B1 and zearalenone from feed utilizing monoclonal antibodies against aflatoxin B1 and zearalenone 234…”
Section: Nanotechnology In Animal Production/reproduction and Animal mentioning
confidence: 99%
“…The feed conversion ratio for the broilers did not differ between the treatment groups, which is accordance with the findings in quail 8 and broiler chickens 27 provided with silver nanoparticles via the drinking water, but not with data from weanling pigs supplemented with silver nanoparticle powder in the diet. 7 These conflicting results suggest that poultry species are either less sensitive to silver nanoparticle treatment than pigs, or that silver nanoparticles in powdered form provided via the feed is submit your manuscript | www.dovepress.com…”
Section: Growth Performancementioning
confidence: 94%
“…4 Recently, renewed research interest has been directed towards use of silver as an alternative antimicrobial agent. [5][6][7] Metallic silver compounds and their ions have long been known to have unique antibacterial properties. Silver has been used since time immemorial for the treatment of burns, wounds, and bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation